An Experimental Model of Prolonged Esophagitis With Sphincter Failure in the Rat and the Therapeutic Potential of Gastric Pentadecapeptide BPC 157 - Igor Petrovic; Ivan Dobric; Petar Drvis; Drazen Shejbal; Luka Brcic; Alenka Boban Blagaic; Lovorka Batelja; Neven Kokic; Ante Tonkic; Stjepan Mise; Tomislav Baotic; Mario Staresinic; et al. (Journal of Pharmacological Sciences, 2006)
We report a simple novel rat model that combines prolonged esophagitis and parallel sphincters failure. The anti-ulcer gastric pentadecapeptide BPC 157, which was found to be stable in gastric juice, and is being evaluated in inflammatory bowel disease trials, is an antiesophagitis therapy that recovers failed sphincters. Twelve or twenty months after the initial challenge (tubes sutured into sphincters for one week and then spontaneously removed by peristalsis), rats exhibit prolonged esophagitis (confluent hemorrhagic and yellowish lesions, thinner epithelium and superficial corneal layer, with stratification derangement); constantly lowered pressure of both sphincters (assessed by using a water manometer connected to the drainage port of a Foley catheter implanted into the stomach either through esophageal or duodenal incision); and both lower esophageal and pyloric sphincter failure. Throughout the esophagitis experiment, BPC 157 was given at either 10 µg/kg, i.p., once a day (last application 24 h before assessment) or alternatively, it was given continuously in drinking water at 0.16 µg/ml (12 ml/rat). This treatment recovers i) esophagitis (macroscopically and microscopically, at either region or investigated time period) and ii) pressure in both sphincters (cmH2O). In addition, BPC 157 (10 µg/kg) or saline (1 ml/rat, 5 ml/kg) was specifically given directly into the stomach; pressure assessment was performed at 5 min thereafter. The effect of BPC 157 is specific because in normal rats, it increases lower esophageal sphincter-pressure, but decreases pyloric sphincter-pressure. Ranitidine, given as the standard drug using the same protocol (50 mg/kg, i.p., once daily; 0.83 mg/ml in drinking water; or 50 mg/kg directly into the stomach) had no effect. Keywords:: BPC 157, esophagitis, sphincter (rat)